Keanekaragaman Serangga pada Tanaman Akasia (Acacia nilotica) Di Savana Bekol Taman Nasional Baluran Situbondo Jawa Timur - Saiful Bahri; Nirmala Fitria Firdhausi; Esti Tyastirin; Intan Ahmad (Biotropic : The Journal of Tropical Biology, 2022)
Baluran National Park Situbondo have function to field study, and plays a role as the ecotourism area. Bekol savanna is part of Baluran National Park which has been invaded by Acacia (A. nilotica) plants. The aim of this study was to determine the diversity and abundant of the insects in A. nilotica in Bekol savannas park, Baluran national park. The research method has been employed with the make plots in the savannas dimensions of 20 x 20 m. Insect was collected by flying trap without antractan for four weeks. Insect identification was carried out at Entomology Laboratory SITH ITB. Diversty index was analyzed by Shannon’s index and abundant index with the Simpson’s index. The results showed that the 527 insects caught consisted of 5 insect orders that lived on A. nilotica in the Bekol Savanna . Diversity of insect have the range medium from H= 1,73186 – 2,29266. Insect diversity has high in the plot III and low from plot II. Abundant index was known that the familia Formicidae is dominance species with Polyrhachis sp=45,77465 % plot I, Crematogaster sp= 62,2807% plot II, Crematogaster sp= 45,45455% plot III and plot IV Crematogaster sp= 38,67925%. The low of diversity index because just many insect could live in the A. nilotica and some species likes Caryedon serattus, Zyras compressicornis, Crematogaster sp and Trigona lavaiceps was collected from four site reseach. The abundant of familia Formicidae because they have mutuallystic symbiosis with the A. nilotica. From the result we could conclude that diversity and abundant insect dependent to the plant and interaction have done.